Hydro(radio)chemical relationships in the giant Guarani aquifer, Brazil - Bonotto, Daniel Marcos [UNESP] (Elsevier B.V., 2006)
This investigation was carried out within the Parana sedimentary basin and involved the sampling of 78 pumped tubular wells for evaluating the hydrochemistry and radioactivity due to the nuclides (238)U, (234)U, (222)Ra, (226)Ra, and (228)Ra in the Brazilian part of Guarani aquifer. Several significant correlations were found involving the geostatic pressure, for instance, specific flow rate, CO(3)(2-), SO(4)(2-) temperature, dissolved O(2), free CO(2), pH, redox potential Eh, conductivity, Na, HCO(3)-, CO(3)(2-) , SI(calcite), Cl(-), F(-), SO(4)(2-), and B. Carbonates precipitation was evidenced by inverse correlation between CO(3)(2-) and Ca, Mg, Sr, and Ba, whereas Na exhibited an opposite trend, dissolving rather than precipitating with increasing CO(3)(2-) concentration. An inverse correlation between 3 and K was found, possibly related to the increasing tendency of K to recombine with the thickness of the clayey layers. HCO(3)-played an important role on Na, Ca, Mg, and Sr dissolution. The dissolved U content and (234)U/(238)U activity ratio data were plotted on a two-dimensional diagram that was successfully utilized on identifying an unreported zone of U accumulation, though not necessarily of economic size and grade. The variability in chemical and radionuclides data indicated an important influence of the underlying Paleozoic sediments in the composition of waters from Guarani aquifer. The available data allowed estimate the groundwater residence time by two U-isotopes disequilibrium methods. Values of 45-61 ka were initially calculated, depending on the adopted porosity (15-20%), but a longer residence time (- 640 ka) was also estimated, which is more compatible with the hydraulic conductivity data in Guarani aquifer and groundwater flow velocity occurring at Milk River aquifer, Alberta, Canada. Such time range agrees with previously reported (14)C ages exceeding 30 ka BP at the more central parts of the Parana sedimentary basin. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: groundwater; hydrochemistry; Guarani aquifer; uranium isotopes